2019
DOI: 10.1002/ddr.21531
|View full text |Cite
|
Sign up to set email alerts
|

8‐Hydroxyquinolines are bactericidal against Mycobacterium tuberculosis

Abstract: There is an urgent need for new treatments effective against Mycobacterium tuberculosis, the causative agent of tuberculosis. The 8‐hydroxyquinoline series is a privileged scaffold with anticancer, antifungal, and antibacterial activities. We conducted a structure–activity relationship study of the series regarding its antitubercular activity using 26 analogs. The 8‐hydroxyquinolines showed good activity against M. tuberculosis, with minimum inhibitory concentrations (MIC90) of <5 μM for some analogs. Small su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
1
11
0
2
Order By: Relevance
“…It has been demonstrated that the cloxyquin exhibited bactericidal activity against replicating M . tuberculosis (Odingo et al, ) The present study showed that cloxyquin ( 2 ) displayed the similar values of MIC and MBC against the MSSA and MRSA strains (Table ). It was suggested that cloxyquin has the iron chelating property to compete with the essential nutrient of the microorganisms (Boda, Pandit, Garai, Pal, & Basu, ).…”
Section: Discussionsupporting
confidence: 62%
“…It has been demonstrated that the cloxyquin exhibited bactericidal activity against replicating M . tuberculosis (Odingo et al, ) The present study showed that cloxyquin ( 2 ) displayed the similar values of MIC and MBC against the MSSA and MRSA strains (Table ). It was suggested that cloxyquin has the iron chelating property to compete with the essential nutrient of the microorganisms (Boda, Pandit, Garai, Pal, & Basu, ).…”
Section: Discussionsupporting
confidence: 62%
“…Compounds were tested for cytotoxicity against HepG2 cells as previously described. 48 , 69 , 70 Briefly, cells were exposed to compounds for 48–72 h, and viability was measured using CellTiter-Glo (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…High nitroxoline concentrations in urine and prostate tissue can be achieved with oral therapy compared to lower systemic concentrations ( Dufour and Bollack, 1979 ; Mrhar et al, 1979 ; Wijma et al, 2018 ). Activity against some mycobacterial quality control strains ( Mycobacterium bovis BCG ATCC 35734 and M. tuberculosis H37rv) has been demonstrated ( Odingo et al, 2019 ; Shah et al, 2016 ; Murugasu-Oei and Dick, 2001 ) yet data on clinical isolates, especially with respect to otherwise drug resistant MTB are lacking. In this study, we therefore assessed nitroxoline MICs of clinically isolated mycobacteria including MDR-TB isolates to investigate repurposing of nitroxoline for mycobacterial infections in the era of antimicrobial resistance.…”
Section: Introductionmentioning
confidence: 99%